Pengaruh Pengalaman Merek, Kepercayaan dan Kepuasan dalam Membangun Merek: Loyalitas; Sebuah Penelitian Empiris Tentang Merek Kosmetik Ramah Lingkungan - Pasya Istiara Dhea; Anton Agus Setyawan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The purpose of this study is to analyze the impact of brand experience, brand trust, and brand satisfaction on brand loyalty for environmentally friendly cosmetic products, with a focus on consumers who have purchased and used the product. This research employs a quantitative approach with purposive sampling techniques, involving 200 respondents. Data collection was conducted using a questionnaire that assessed aspects such as brand experience, satisfaction, trust, and brand loyalty. The analysis method used is Partial Least Squares-Structural Equation Modeling (PLS-SEM) with the help of SmartPLS software. The results indicate that brand experience, brand trust, and brand satisfaction have a positive and significant effect on brand loyalty, with a significance value of 0.000 (p < 0.05). These findings provide valuable insights for marketers to strengthen brand loyalty by enhancing positive brand experiences, maintaining product communication transparency, and increasing consumer engagement through social media and loyalty programs.